An Introductory Study on the Writings of Sir Syed Ahmed Khan on Seerat other than “Khutbaat e Ahmadiya” - Syed Aziz Ur Rahman (jihat-ul-islam, 2020)
Sir Syed Ahmed Khan is one of the most prominent names in Urdu literature. His contributions in the world of knowledge, wisdom and services to mankind are manifold like reformation, education, research and administrative services. Sir Syed has written on wide variety of subjects including pure religious writings and his writings has remained point of discussion and debate in religious and academic circles. Large part of Sir Syed’s religious writing is devoted on subject of the life of Holy Prophet Muhammad (S.A.W). The most important is his book “Khutbaat-e-Ahmedia”and “Molood Nama- Jala ul’ quloob”, but his other writing on Seerat doesn’t often discussed. The main reason for neglecting Sir Syed’s other writings on Seerat is our lack of awareness and knowledge towards them as to satisfy ourselves we only give speeches on Sir Syed. To understand the true services of Sir Syed and set its due importance we need to read his writings on seerat with proper context, otherwise, it is difficult to draw any opinion about his work. Having this background in our mind this paper will introduce Sir Syed’s writing onSeerat. Since too much is written on Khutbaat e Ahmedia, so discussion on it will be avoided in this article. Although, there is a dire need of critical and analytical work on Sir Syed’s writings on life of prophet Muhammad (S.A.W) but this paper will only deal with introduction on the subject with some supplementary debates and references.